Burundi : Fourth Review Under the Extended Credit Facility Arrangement. (IMF Staff Country Reports; Country Report ;, 2014)
Burundi's Fourth Review Under the Extended Credit Facility (ECF) Arrangement is discussed. The measures undertaken to enhance fiscal outlook by the 2015 elections are reviewed. Satisfactory progress has been made on structural reforms. Policy discusses have focused on reinvigorating program implementation after the difficulties in completing the third review under the ECF arrangement. The IMF staff recommends the completion of the fourth review under the ECF arrangement, setting of new performance and indicative criteria for September 2014, and the disbursement of SDR 5 million.